Ratio Decidendi Dari Putusan Mahkamah Agung Nomor 2086 K/Pid.Sus/2023 Terhadap Penjual Dan Pembeli Jual Beli Konten Pornografi - Mohammad Afrizal; Made Warka (Pusat Riset dan Inovasi Nasional, 2024)
The author raises a case from the Supreme Court Decision Number 2086 K/Pid.Sus/2023 with the defendant Gusti Ayu Dewanti with the pseudonym Dea Onlyfans who was proven to have legally violated a criminal act of pornography or committed a criminal act of pornography by offering and selling pornographic content on the onlyfans site. The author needs to consider in more depth the Ratio Decidendi or Consideration of the Judge who some time ago just handed down a decision on this case, considering the decision given to the litigants and also the decision made by the defendant and witnesses which was decided by the judge in relation to the case, one of the buyers in this case, one of the famous comedians, Marcel Widianto, was not involved in a crime. He was one of the buyers who indirectly supported what the defendant was doing. From this case, it was found that the existing law is unclear/vague under existing supervision, where someone who has supported a buying and selling transaction by purchasing pornographic content on social media can be free from criminal law. The impact that will occur if this happens in the future, many buyers or purchasers of pornographic content will have more opportunities to carry out their activities. This can also worsen the standards that apply in Indonesian society because the influence of explicit entertainment is very detrimental to the country's ethics, both adults and children. Therefore, the author wants to examine the formulation of the problem, namely, what is the Decidendi Ratio from the Supreme Court Decision Number 2086 K/Pid.Sus/2023 regarding Sellers and Buyers of buying and selling pornographic content?